PENGARUH PERBANDINGAN TEPUNG KIMPUL (Xanthosoma sagittifolium) DAN PASTA DAUN PEGAGAN (Centella asiatica) TERHADAP KARAKTERISTIK COOKIES - Ariyasa, I Kadek; Ina, Putu Timur; Arihantana, Ni Made Indri Hapsari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 4 (2018): Jurnal ITEPADO - 10.24843/itepa.2018.v07.i04.p09, 2018)
This study aims to determine the effect of comparison of Xanthosoma flour with Centella leaf paste to the characteristics of cookies produced and the comparison between Xanthosoma flour with Centella leaf paste that is able to produce cookies with the best characteristics. The experimental design used was Block Randomized Design with treatment factor that is the comparison of Xanthosoma flour and Centella leaf paste consisting of 6 levels: 95%:5%; 92%:8%; 89%:11%; 86%:14%; 83%:17%; 80%:20%. The treatment was repeated 3 times to obtain 18 units of experiment. The data obtained were analyzed by ANOVA and if the treatment had a significant effect on the observed variables then continued with Duncan test. The comparison of Xanthosoma flour with Centella leaf paste affected the content of water, coarse fiber, total chlorophyll, vitamin C, antioxidant activities, texture (hedonic and scoring test), aroma (hedonic test), taste (hedonic test) and overall acceptance (hedonic test) and also had no significant effect on color (hedonic test) of cookies. Comparison of 89% Xanthosoma flour : 11% Centella leaf paste had the best characteristics of cookies with content of water 4.41%, coarse fiber 7.21%, total chlorophyll 2.51 mg/kg, vitamin C 1.54 mg/g, antioxidant activities (based on IC 50 ’s value) 65.61%,  the aroma was rather liked, the texture was rather liked and crunchy, the color, taste, and overall acceptance liked.